Role of exosomal competing endogenous RNA in patients with hepatocellular carcinoma. Issue 10 (17th July 2018) - Abd El Gwad, Asmaa; Matboli, Marwa; El‐Tawdi, Ahmed; Habib, Eman K.; Shehata, Hanan; Ibrahim, Doaa; Tash, Fathy
Abstract: Recent research has tried to use exosomal RNAs (coding and noncoding) as potential diagnostic markers for hepatocellular carcinoma (HCC). Initially, by using bioinformatics, we selected an HCC‐exosomal RNA‐based biomarker panel. The choice of this panel depends on the integration of Ras‐related in brain ( RAB11A ) gene expression and its competing endogenous network. This network includes long noncoding RNA RP11‐513I15.6 ( lncRNA‐RP11‐513I15.6 ) and microRNA‐ 1262 ( miR‐1262 ). Secondly, we tried to validate the expression of this network in the sera of 60 patients with HCC in comparison with 42 chronic hepatitis C virus‐infected patients and 18 healthy controls. Then we assessed the diagnostic efficiency of this panel using a receiver operating characteristic curve analysis. The panel of 3 exosomal RNA‐based biomarkers ( lncRNA‐RP11‐513I15.6, miR‐1262, and RAB11A) showed excellent sensitivity and specificity in discriminating patients with HCC from patients with chronic hepatitis C virus and healthy controls. Among these 3 RNAs, serum RAB11A mRNA was the most independent prognostic factor. The selected circulatory exosomal RNA‐based biomarker panel showed its ability to be used as a diagnostic and prognostic biomarker tool for HCC. Moreover, these biomarkers could be therapeutic targets. Abstract : To best of our knowledge, this is the first study that addresses the exosomal competing endogenous RNA panel (lncRNA‐RP11‐513I15.6, RAB11A mRNA, and miR‐1262) that could be used as a diagnostic and prognostic tool for hepatocellular carcinoma.